Distribution of thermal characteristics in the central part of the south-western side of the Dnieper-Donets basin - Usenko, A.P. (Reports of the National Academy of Sciences of Ukraine, 2017)
The regularities of the distributions of geothermal gradients and heat flows on 15 fields of the south-western side of the Dnieper-Donets basin are analyzed. The distributions of geothermal parameters on gas and oil fields are compared. The dependence of gradients on the tectonic structure (location of hydrocarbon deposits and placement of faults) and on the depth of manifestation of the hydrogeological inversion is studied. It is concluded that the presence and the location of hydrocarbon deposits are likely related to the inflow of a deep hydrothermal solution via permeable fault zones.